1981
DOI: 10.1177/030006058100900403
|View full text |Cite
|
Sign up to set email alerts
|

Flufenamic Acid and Placebo Compared in Rheumatoid Arthritis and Osteoarthritis

Abstract: Forty patients in general practice with rheumatoid arthritis or osteoarthritis were identified as suffering from moderate pain and tenderness and moderate stiffness in excess of 30 minutes. After discontinuation of non-steroidal anti-inflammatory drugs for 2 weeks, a crossover study was conducted comparing the benefits of flufenamic acid, 100 mg, four times daily with placebo. At the same time, paracetamol at a dose up to 8 x 500 mg daily, could be used for pain which the patient judged to be unrelieved. Thirt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…FA acts not only as an anti-inflammatory drug [37], but also as an adjuvant for adipogenic differentiation. This NSAID can be easily obtained, is not expensive and is already approved by FDA to treat several diseases, such as rheumatic arthritis, which constitute significant advantages for its clinical use [43,44]. Therefore, implication of FA in future ATE applications could be considered a safe and economical choice.…”
Section: Discussionmentioning
confidence: 99%
“…FA acts not only as an anti-inflammatory drug [37], but also as an adjuvant for adipogenic differentiation. This NSAID can be easily obtained, is not expensive and is already approved by FDA to treat several diseases, such as rheumatic arthritis, which constitute significant advantages for its clinical use [43,44]. Therefore, implication of FA in future ATE applications could be considered a safe and economical choice.…”
Section: Discussionmentioning
confidence: 99%
“…Although other, potentially harmful effects on the human eye have to be ruled out, flufenamic acid -with its long history of being used in the treatment of rheumatoid disorders, 8 and its potentially pressure reducing 7 and neuroprotective properties 9 - may be of interest in the search for new drugs to combat glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…5 Previous research has shown that flufenamic acid is a substance that relaxes trabecular meshwork more strongly than ciliary muscle and might therefore lower intraocular pressure. 7 This drug, a non-steroidal anti-inflammatory compound which is used in the treatment of rheumatoid disorders, has already been in use clinically for a long time, 8 although not in the treatment of glaucoma. The fact that flufenamic acid has recently been shown to display neuroprotective properties in the retina 9 adds to our interest.…”
Section: Introductionmentioning
confidence: 99%
“…Flufenamic acid, a therapeutically used antirheumatic agent [76, 77, 78], relaxed trabecular meshwork strips precontracted by carbachol or endothelin 1 [32](fig. 5).…”
Section: Contractility Measurementsmentioning
confidence: 99%